(3ef cJGH GdKeQI dHWdjehSs - (3CMeO Hf jhSa GdcGJHs; (3HWdjehSs
(3ChdgG (B:s
(3bGd HWdjehS bO jbOQ GdefLe Ydi OaY cKjQ ef CaYGd GdfLhe EPG cGf YGdekG HWHjYI eG jhJQ ajg GdaYd hhWC ddaYd bHd hbhYg s
(3BNQgG (B:s
(3MJi JWgQ GdhMOI ai GdbGfi ceG WgQJ GdcKQI ai GdChd hgh GdPi jSei SYGOI aGfbWY GdcdGe haGJ Cf fHdY CbUi eG YfOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B13s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
Keywords: (3GdadSaI hGdefWbs